KECERDASAN EMOSIONAL PADA ANAK USIA DINI DI ERA DIGITAL - Celsi Agistania Biot; Patricia Giska Goha; Chelsia Koda; Lyra Gracia Ratu; Gabriel Tumbel Nelwan; Dean Martfend Nampe (PT. Giat Konseling Nusantara, 2026)
In the digital age, emotional intelligence or Emotional Quotient (EQ) is important for children. This study explains what emotions are, but also the role of parents and teachers in building children's EQ in the digital age, as well as the best ways to do so. The research method involved reviewing various scientific sources. Emotional intelligence is defined as a person's ability to control their emotions, both towards themselves and others. Early childhood education is the basic education level for children aged 0 to 6 years. The results show that parents and teachers play a very important role in helping children recognize and manage their emotions. The best ways to do this include using technology wisely, practicing social skills, and creating an environment that supports healthy emotional expression. In conclusion, developing children's EQ in the digital age requires cooperation between parents, teachers, and the positive use of technology.